Kontribusi Kepemimpinan Kepala Sekolah, Budaya Organisasi, Dan Motivasi Kerja Terhadap Kinerja Guru Di MTs Negeri Se-Kabupaten Sragen - KISMANTO, KISMANTO; , Prof. Dr. Bambang Sumardjoko, M.Pd (2016)
Kismanto. Q.100.050.379. Contribution of Principal Leadership, Organizational Culture, and Motivation Work To Performance In MTs Teachers Se Sragen. Thesis University Graduate Program Muhmmadiyah Surakarta. 2016. The purpose of this study was to determine (1) the contribution of school leadership on the performance of teachers at MTs Se-Sragen. (2) the contribution of organizational culture on the performance of teachers at MTs Se-Sragen (3) the contribution of work motivation on the performance of teachers at MTs Se-Sragen (4) the contribution of school leadership, organizational culture and work motivation on performance teacher at MTs Se-Sragen. This research is a quantitative research using citation analysis. This research is classified as quantitative data analysis is a quantitative or statistical. The main subject of this research is the principal and teachers. Data collection techniques used in this study is a questionnaire to fill out a questionnaire and questions of each variable used in this study include the variable of school leadership, organizational culture, motivation and performance. Tenik data analysis in this study using the model 1) Test Instruments Research, includes: validity and reliability testing, 2) Test of linearity, 3) Hypothesis, include: multiple regression analysis, T-test, test F and the coefficient of determination. The results of the research contributions of school leadership, organizational culture and work motivation on teacher performance MTs Se Sragen, the authors obtained the following conclusions: 1) There is a contribution of school leadership on teacher performance of 0.354 and sig = 0.000. which may mean that the contribution of school leadership on teacher performance is very strong and significant in MTs Se Sragen. 2) There is a contribution of organizational culture on performance of teachers by 0158, and sig = 0.000, can be defined that contribute to the organization's culture is very strong and significant performance in MTs Se Sragen. 3) There is a contribution of work motivation on teacher performance for 0511 and sig = 0.000 means that the contribution of employee motivation tehradap teacher performance is very strong and significant in MTs Se Sragen. 4) There is the contribution of school leadership, cultural organizations exist and motivation to work together towards the work of teachers by 39 831 and sig = 0.000, can be interpreted that the contribution of school leadership, organizational culture and work motivation on teacher performance together very strong and significant at MTs Se Sragen. In addition to principal leadership, organizational culture and work motivation together greatly affect the performance of teachers in running performance, this clearly contributes directly from the principal's leadership, organizational culture and work motivation on teacher performance together.